Avaliação técnico-econômica do aumento do rendimento em motores de indução trifásicos de baixa potência após rebobinagem - Aguiar, Victor de Paula Brandão (2018)
Nowadays the economic analysis of electric motor’s life cycle is the most effective way to measure the economic viability of the energy efficiency actions to the end users, specially the industrial sector. The replacement of aged electric motors by new and energy-efficient ones is an well-known trade that leads to energy savings however the cost-effectiveness in motors’ repla- cement does not take into account the life cycle costs, how the efficiency value is measured or calculated, and economical features as the variation and growth of electricity tariff in a local sce- narium. Thus, this work presents the technical feasibility and cost-effectiveness of the low-power induction motors that have their efficiency improved after rewinding aiming better investment viability and presents the value of energy saved promoting energy efficiency. The induction motor’s analysis is performed before and after rewinding, in sequence the motors are simulated by a commercial software based on finite elements method (COMSOL Multiphysicsr). The motors are rewound using a rewinding strategy that use feasible windings at rewinding workshops, i.e., concentric and imbricated windings. The test workbench for efficiency measurement by A and B methods from IEEE 112/2017 makes possible locked-rotor current measurement and winding temperature measurement for each tested motor. Among rewound motors which were simulated and tested, they have the best cost-effectiveness after replacement instead IR3/IE3/Premium motors directly sold in the market and even a hypothetical IE4/Super-Premium motor where an IR4 minimum energy performance standard is proposed to make real this comparison. The rewound motors increase their efficiencies between 3 and 4 percentage points in relation to the former winding and the payback is less than 2 years regardless of the efficiency measurement method used. From the motor with concentric winding and efficiency level IE2/IR2 some rewound motors reach IR3/IE3 with differents imbricated windings and one motor reaches the borderline between IE4/Super-Premium and IR3/IE3 levels.